Referenciação em Cuidados Paliativos: Barreiras à Referenciação pelos Profissionais de Saúde- Scoping Review - Maria Clara Monteiro Pinto Baldaia (2023)
Introduction: Palliative care aims to improve quality of life of patients and their families facing problems associated with life-threatening illnesses. Despite the benefit of early referral, this is still not the most frequent procedure. Objective: Identify and understand the referral barriers to Palliative Care, by healthcare professionals, for adult patients with oncological or non-oncological pathologies, in any activity context. Methods: Scoping Review based on the principles advocated by the Joanna Briggs Institute. The databases consulted were Pubmed, Scopus and Web of Science in June 2023, using the keywords: palliative care AND reference, the time horizon 2013-2023was defined. Of the total of 957 articles found, 15 articles were selected for the review. Results: Patients referral to PC is occurring late and, mostly, when the patient has no symptomatic control and treatment options are exhausted. Three main categories of referral barriers were identified: providers- related, healthcare system related and patient- related. Conclusions: Although healthcare professionals recognize the value and the importance of PC, there is some resistance to referral. Access to palliative care requires multiple sectors working together to address patients' needs. Investment in training new professionals and improving access to services and resources is essential.